Synthesis and Characterization of rGO Using a Combination Hummers Method and Hydrothermal Reduction - Maichel Letare Pardede; Nicholas Jonathan; Robin Irawan; Agung Nugroho; Ratna Frida Susanti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Reduced graphene oxide (rGO) was successfully synthesized through a combination of two oxidation methods. The Hummers method was employed to synthesize graphite oxide (GrO), followed by a hydrothermal reduction technique to obtain a more ordered rGO structure. X-ray diffraction (XRD) analysis confirmed the transformation of GrO to rGO, as indicated by an interlayer spacing of 0.35–0.40 nm. This value reflects the crystalline characteristics and multilayer nature of the structure. The calculated crystallite size yielded La = 5.825 nm and Lc = 0.967 nm, suggesting a relatively high degree of crystallinity. Raman spectroscopy revealed an increase in structural disorder after the reduction process, as shown by an ID1/IG ratio of 1.771, which indicates the formation of structural defects due to the removal of oxygen-containing groups. Meanwhile, the IG/ID3 ratio of 1.039 confirms that the carbon atoms in rGO are arranged in a hexagonal graphite lattice. Additionally, the I2D/IG ratio of 0.321 indicates the presence of a multilayer structure. Scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX) showed that the rGO consists of graphene layers exhibiting folding and wrinkling, likely caused by thermal fluctuations during reduction at 180°C. The success of the reduction process was further supported by the increase in the C/O ratio from 2.42 in GrO to 5.39 in rGO. Electrochemical characterization by cyclic voltammetry (CV) demonstrated that rGO exhibits pseudocapacitive behavior, achieving a specific capacitance of 408.661 F/g at a scan rate of 5 mV/s. Overall, the combined synthesis approach employed in this study successfully produced rGO with favorable morphology and promising electrochemical properties, highlighting its potential for energy storage applications such as supercapacitors.